2016
DOI: 10.1002/hep.28682
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C‐C motif) receptor 2–positive monocytes aggravate the early phase of acetaminophen‐induced acute liver injury

Abstract: Infiltrating monocyte-derived macrophages aggravate APAP hepatotoxicity, and the pharmacological inhibition of either CCL2 or CCR2 might bear therapeutic potential by reducing the inflammatory reaction during the early phase of AILI. (Hepatology 2016;64:1667-1682).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
273
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(306 citation statements)
references
References 41 publications
14
273
0
1
Order By: Relevance
“…As such, therapeutic options that target the later stages of the injury have become the most probable for improving patient survival and reducing the number of transplants needed. While the initial stage of toxicity is mediated by reactive metabolite formation and mitochondrial dysfunction (reviewed in [48,49], a number of studies during the last decade have suggested a later stage of injury that is potentially mediated, at least in part, by the recruitment of inflammatory leukocytes such as neutrophils and monocytes [22,50-53]. One common explanation for the recruitment of these inflammatory cells is activation of the inflammasome through release of local DAMPs and other cellular constituents [22,54].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, therapeutic options that target the later stages of the injury have become the most probable for improving patient survival and reducing the number of transplants needed. While the initial stage of toxicity is mediated by reactive metabolite formation and mitochondrial dysfunction (reviewed in [48,49], a number of studies during the last decade have suggested a later stage of injury that is potentially mediated, at least in part, by the recruitment of inflammatory leukocytes such as neutrophils and monocytes [22,50-53]. One common explanation for the recruitment of these inflammatory cells is activation of the inflammasome through release of local DAMPs and other cellular constituents [22,54].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, cytokines (e.g., TNF-α, IL-1β, IL-6, IL-10) and chemokines (e.g., MCP-1, MIP-2, IL-8) are detectable in plasma of animals and patients after APAP overdose [67-74]. These pro-inflammatory mediators can activate and recruit first neutrophils [50,67,75] and later monocytes [53,68,76] to the liver (Figure 3). Despite these effects, the pathophysiological role of this sterile inflammatory response after APAP remains a topic of considerable debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cenicriviroc (CVC), an oral antagonist of both, CCR2 and CCR5-dependent pathways, results in a potent inhibition of inflammatory response and fibrogenesis in diverse preclinical models of hepatic fibrosis (63,146). In line with that, several trials currently address the clinical usefulness of CVC.…”
Section: Cenicrivirocmentioning
confidence: 99%
“…In real conditions -especially in human diseases -macrophages are highly plastic and integrate multiple signals to shape their response (102). For instance, in the injured liver macrophages often express markers of inflammation or resolution simultaneously (103) and can rapidly change their phenotype depending on the hepatic microenvironment (104). Thus, much more efforts should be done to identify and characterize these important cells in relations to different diseases and different stages of the same diseases.…”
Section: Hepatic Macrophages As Theragnostic Biomarkersmentioning
confidence: 99%